Circular economy tourist practices. Issue 22 (16th November 2020) - Sørensen, Flemming; Bærenholdt, Jørgen Ole; Greve, Kim Andreas Gjetting Møller
ABSTRACT: This research letter presents the findings of a Delphi study on the possible future development of circular economy (CE) principles in tourism. In contrast to the few existing CE studies in tourism research, which focuses on how companies may apply CE production principles, the Delphi study presented here suggests how tourists' practices may support the development of a CE in tourism. Further, the findings indicate drivers, complexities, paradoxes and barriers for such practices' future development.